COMMITMENT, COMMUNITY AND BRAVERY: THE CORE ACTIVITIES IN ENDORSING SPEAKING SKILL BY ENGLISH CAMP PROGRAM - Nanan Abdul Manan (University of Kuningan, 2018)
Speaking skill is the prominent thing in verbal communication due to most students of university got the difficulties in practicing it. English camp program becomes a way out to boost students’ speaking performance. Hence, this research is aimed to know the English speaking competence by means of English Camp Program (ECP). By applying a case study, some students of Mathematic Education of STKIP Muhammadiyah Kuningan were chosen as the participants. The research concerns on the three categories of ECP activities; commitment, community, and bravery. Those factors are so simple but they are very important to lead the students to practice English speaking, to create natural situation in practice and to strengthen their English speaking performance. This study revealed that ECP gives a positive impact on students’ speaking skill. ECP can give a new experience of students who join the English Program without any obstacles in practicing; many chances, free topics and experience exploration. ECP is a simple activity that can create a big result in speaking English skill.Keywords: English camp program, speaking skill, commitment, community, bravery